Exploiting sterility and fertility variation in cytoplasmic male sterile vegetable crops. Issue 1 (31st January 2022) - Xu, Fengyuan; Yang, Xiaodong; Zhao, Na; Hu, Zhongyuan; Mackenzie, Sally A; Zhang, Mingfang; Yang, Jinghua
Abstract: Cytoplasmic male sterility (CMS) has long been used to economically produce hybrids that harness growth vigor through heterosis. Yet, how CMS systems operate within commercially viable seed production strategies in various economically important vegetable crops, and their underlying molecular mechanisms, are often overlooked details that could expand the utility of CMS as a cost-effective and stable system. We provide here an update on the nature of cytoplasmic–nuclear interplay for pollen sterility and fertility transitions in vegetable crops, based on the discovery of components of nuclear fertility restoration and reversion determinants. Within plant CMS systems, pollen fertility can be rescued by the introduction of nuclear fertility restorer genes ( Rfs ), which operate by varied mechanisms to countermand the sterility phenotype. By understanding these systems, it is now becoming feasible to achieve fertility restoration with Rfs designed for programmable CMS-associated open reading frames ( ORFs ). Likewise, new opportunities exist for targeted disruption of CMS-associated ORFs by mito-TALENs in crops where natural Rfs have not been readily identified, providing an alternative approach to recovering fertility of cytoplasmic male sterile lines in crops. Recent findings show that facultative gynodioecy, as a reproductive strategy, can coordinate the sterility and fertility transition in response to environmental cues and/or metabolic signals that reflect ecological conditions of reproductive isolation. This information is important to devising future systems that are more inherently stable.